Role of Radiotherapy in Modern Treatment of Hodgkin's Lymphoma - Kheng-Wei Yeoh; N. George Mikhaeel (Advances in Hematology)
Hodgkin's Lymphoma was incurable until the advent of effective therapeutic radiation around the first half of the 20th century. As survival rates improved, the long-term toxicities from radiotherapy began to emerge. This together with the availability of effective chemotherapy has encouraged a combined modality approach for early-staged disease and the omission of radiotherapy in advanced-staged disease. The differing toxicities of radiotherapy and chemotherapy has promoted ongoing research to identify the utility of each of these modalities in the modern management of Hodgkin's Lymphoma. This article will provide a critical review of the developments and indications for modern radiotherapy, in context with advances in chemotherapy, for the treatment of Hodgkin's Lymphoma.